Age dependence of otoacoustic emissions: the loss of amplitude is primarily caused by age-related hearing loss and not by aging alone - Hoth, Sebastian; Gudmundsdottir, Katrin; Plinkert, Peter K. (European archives of oto-rhino-laryngology and head & neck, 2010)
The amplitude of otoacoustic emissions (OAE) is known to decrease with increasing age, but it is still unclear whether this is due to aging alone or to age-related hearing loss. This study describes the exploration of a large database (5,142 patients from 0.4 to 89.8 years) collected in a routine clinical testing. Reliable pure tone audiograms, transitory evoked otoacoustic emissions (TEOAE) and distortion product otoacoustic emissions (DPOAE) recordings were available from 5,424 ears without conductive loss, acute sudden deafness or retrocochlear disorder. From this database, group 1 with behavioral thresholds of 10 dB HL or better at all frequencies from 1 to 4 kHz and group 2 with age-accordant thresholds after ISO 7029 were formed. In both groups, the OAE amplitude decreased with increasing age, but in group 1, the effect was significant only for DPOAE recorded at 3 and 4 kHz. In group 2, the loss of amplitude was steeper and highly significant for TEOAE as well as DPOAE at all frequencies, but most pronounced at high frequencies. These findings support the hypothesis that the reduction of OAE amplitude with increasing age is primarily caused by age-linked hearing loss and not by aging alone.